Machine Learning Applied to Optical Communication Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint explores how machine learning is revolutionizing optical communication systems, featuring topics ranging from long-haul coherent links and short-reach IM/DD systems to PONs, VLC, and chaos-based secure communication. Covering neural network equalization, optical signal processing, and system-level intelligence, this collection highlights cutting-edge research and future directions at the intersection of AI and photonics.